EFFICACY OF THORACIC SEGMENTAL SPINAL ANESTHESIA ALONG WITH UNILATERAL ERECTOR SPINAE BLOCK IN PATIENTS UNDERGOING UNILATERAL MODIFIED RADICAL MASTECTOMY AND AXILLARY DISSECTION: A NOVEL MULTICENTRIC STUDY - DESHPANDE, NANDINI; AGARWAL, KAPIL; HATGAONKAR, ROHIT; PALIWAL, NARESH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to find out the efficacy of thoracic segmental spinal anesthesia combined with unilateral erector spinae block in patients undergoing unilateral modified radical mastectomy and axillary lymph node dissection Methods: This was a prospective cohort study in which 40 patients with carcinoma breast undergoing modified radical mastectomy with axillary dissection under thoracic segmental spinal anesthesia combined with unilateral erector spinae block were included on the basis of a predefined inclusion and exclusion criteria. Erector spinae plane block was given at T5 level and thoracic spinal anesthesia was then given at T5–T6 level in the same position by median or paramedian technique. Patients were assessed for severity of pain by visual analog scale score till 24 h of surgery. Results: The mean age of studied cases was found to be 44.12±10.04 years. Mean weight of studied cases was 54.38±9.8 kg, whereas mean duration of surgery was found to be 98.24±16.86 min. The most common American Society of Anesthesiologists (ASA) grade to which patients belonged was found to be ASA III (55%) followed by ASA II (30%) and ASA I (15%). Eleven patients required rescue analgesia within first 24 h after surgery and mean doses of rescue analgesia in 1st 24 h after surgery was found to be 0.92±0.48. Four (10%) patients developed hypotension, whereas three (7.5%) patients had bradycardia. However, all these 7 (17.5%) had transient bradycardia or hypotension which could be managed by IV Atropine or IV mephentermine and fluid bolus. Conclusion: Thoracic segmental spinal anesthesia combined with unilateral erector spinae block is an excellent option for patients undergoing modified radical mastectomy with axillary dissection.